Control del inventario y su incidencia en la información contable de la Bananera Reybapac de la parroquia San Juan, período 2021. - Mestanza Ortiz, Denisse Darly (2023)
This case study was carried out in the Reybanpac banana plantation. The objective is to determine inventory control. The methodology used consists of a research with a non- experimental design, mixed approach, descriptive, field and documentary research type, inductive-analytical methods, interview techniques and their respective instruments. The results are: the main problems that arise in inventory management are related to the management and control of inventory; Companies record income and expenses; IAS 2 does not apply to the treatment of accounting information related to inventories, but guidelines from other control organizations are followed; and inventory management has a weakness because it has a risk of 76.25% that must be managed to avoid problematic situations. In conclusion, the benefits derived from good inventory management include determining which products have the highest and lowest turnover; the company's human talent does not consider the application of IAS 2 in the management of accounting information of inventory accounts; There is a low level of reliability and a high level of risk, which explains the inconveniences associated with inventory management and processing accounting information.